CAFFEIC ACID PHENETHYL ESTER (CAPE) MEDIATED DECREASE IN METASTASIS OF COLON CANCER CELLS: AN IN VITRO AND IN VIVO STUDY - Wu, Weiqiang; Gao, Feng; Song, Xi Heng, Feng; Zhao, Yong; Xu, Ming; Zhang, Xin; Yang, Zengqiang (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Caffeic acid phenethyl ester (CAPE) is a phytochemically active component obtained from honeybee hivepropolis. CAPE has been reported to show antimitogenic, anticancer, and other beneficial medicinal properties. Many of itsactivities have been reported to be mediated by inhibiting levels of matrix metalloproteinase, that is, MMP-2 and MMP-9.We hypothesize the effect of CAPE on the metastasis of colon cancer cells in both in vitro and in vivo.Methods: Cell migration, motility, invasion were evaluated also expression of protein and matrix metalloproteinases(MMPs) such as MMP-2 and MMP-9 were measured in SW-480 cancer cells in vitro. The cells were exposed to Phorbol12-myristate 13-acetate (PMA) and were treated with various concentration of CAPE.Results: The treatment of CAPE caused significant decrease (P<0.05) in both cell motility and invasion. The treatment ofCAPE inhibited activity of MMP-2 and MMP-9 and their protein with increasing dose in SW-480 cancerous cells. Antimetastaticactivity was evaluated in vivo in BALB/c mice by injecting them with CT-26 mouse colon cancer cells via tailvein and were treated with CAPE (20 mg/kg) orally for 21 days. The CAPE treatment significantly (P<0.05) reduced countof pulmonary nodules. The mice showed decreased plasma MMP-2 and MMP-9 activity after 21 days treatment withCAPE.Conclusion: The study suggested beneficial role of CAPE in preventing invasion of colon cancer and metastasis via MMP-2 and MMP-9 mediated pathway.